2005
DOI: 10.1111/j.1365-2486.2005.001031.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fluxes from a tropical peat swamp forest floor

Abstract: A tropical ombrotrophic peatland ecosystem is one of the largest terrestrial carbon stores. Flux rates of carbon dioxide (CO 2 ) and methane (CH 4 ) were studied at various peat water table depths in a mixed-type peat swamp forest floor in Central Kalimantan, Indonesia. Temporary gas fluxes on microtopographically differing hummock and hollow peat surfaces were combined with peat water table data to produce annual cumulative flux estimates. Hummocks formed mainly from living and dead tree roots and decaying de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
248
4
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(278 citation statements)
references
References 37 publications
20
248
4
6
Order By: Relevance
“…Methane fluxes measured here were several orders of magnitude lower than CO 2 fluxes and varied markedly among sites. The highest CH 4 fluxes from site 1 (R. taedigera) and site 5 (sawgrass swamp) are comparable to fluxes reported in the literature from Kalimantan(e.g., 0.35-2 mg CH 4 m -2 h 1 ; Furukawa et al 2005;Hadi et al 2005;Jauhiainen et al 2005), while the lowest CH 4 fluxes at the three intermediate sites in the current study (C. panamensis and mixed forest) are comparable to those reported for Sarawak wetlands (maximum rates of 11.2 lg CO 2 m -2 h -1 ; Melling et al 2005a, b). Our results suggest that CH 4 fluxes have high spatial variability in peatland systems and vary in response to differences in the water table Hadi et al 2005;Jauhiainen et al 2005) and substrate availability (Bachoon and Jones 1992) to a greater extent than CO 2 fluxes.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Methane fluxes measured here were several orders of magnitude lower than CO 2 fluxes and varied markedly among sites. The highest CH 4 fluxes from site 1 (R. taedigera) and site 5 (sawgrass swamp) are comparable to fluxes reported in the literature from Kalimantan(e.g., 0.35-2 mg CH 4 m -2 h 1 ; Furukawa et al 2005;Hadi et al 2005;Jauhiainen et al 2005), while the lowest CH 4 fluxes at the three intermediate sites in the current study (C. panamensis and mixed forest) are comparable to those reported for Sarawak wetlands (maximum rates of 11.2 lg CO 2 m -2 h -1 ; Melling et al 2005a, b). Our results suggest that CH 4 fluxes have high spatial variability in peatland systems and vary in response to differences in the water table Hadi et al 2005;Jauhiainen et al 2005) and substrate availability (Bachoon and Jones 1992) to a greater extent than CO 2 fluxes.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, potential soil respiration determined on drained samples in the current study showed a clear link to nutrient status. This was not reflected in the pattern of CO 2 flux in the field, however, suggesting that variables other than nutrient status, such as root respiration (Chimner 2004;Metcalfe et al 2007) or water table fluctuations (Jauhiainen et al 2005), regulate the net CO 2 efflux from the peat surface. The CO 2 flux rates were within the range of those measured from lowland forested swamps on deep peat in central Kalimantan, Indonesia (ca.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These destructive activities not only disturb the ecosystem functions, but affect gas fluxes between peatland areas and atmosphere. In addition to reducing the amount of biomass contained by living vegetation, activities in peatland areas cause changes in water table level, which affect peat decomposition and carbon fluxes from peat (Jauhiainen et al 2005). Indirectly, degradation of peatland ecosystems makes them more vulnerable to yearly fire activity (Cochrane 2001;Siegert et al 2001) and increases the risk of periodical severe fire episodes that release high quantities of carbon into the atmosphere (Page et al 2002;Heil et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, information on gas fluxes in both undisturbed (e.g. Jauhiainen et al 2005) and disturbed (e.g. Hirano et al 2007;Jauhiainen et al 2008) conditions are needed for estimation of gas emissions with potentially global consequences.…”
Section: Introductionmentioning
confidence: 99%